Review on advances of airjection irrigation - Yuan, Li; Wenquan, Niu; Jingwei, Wang; Jian, Xu; Mingzhi, Zhang; Kangyong, Li (International Journal of Agricultural and Biological Engineering, 2016)
Air is squeezed out of the soil in the process of traditional irrigation. Hypoxia stress of the root zone is harmful to the yield and quality of crops. It was found that the improvement of the soil oxygen condition can increase the crop yield and quality in the root zone. In recent years, a number of studies showed that hypoxia stress has bad influence on root zone, and the ventilation technologies have some positive effects on crop yield and quality. This paper introduces and analyzes the mechanism of hypoxia stress in root zone, and provides an overview about characteristics and application on airjection irrigation. Simultaneously, the advantages and disadvantages of different airjection irrigation technologies were investigated, the achievements that have been made in this filed were summarized, and some existed problems were discussed. Based on the previous studies, the research trends of the airjection irrigation technology were proposed, which can provide a reference for the further research in the research field.Keywords: irrigation, airjection, root zone, hypoxia stress, crop yieldDOI: 10.3965/j.ijabe.20160902.1361Citation: Li Y, Niu W Q, Wang J W, Xu J, Zhang M Z, Li K Y. Review on advances of airjection irrigation. Int J Agric & Biol Eng, 2016; 9(2): 1－10.